Piagetian 5E Model and Students’ Interest in Chemistry: Facing the Challenges of Global Competitiveness - Opara , Mary Felicia (African Journal of Education,Science and Technology (AJEST), 2013)
The premise of the study was to examine the effect of Piagetian Intelligence 5E model on students‟ interest in Chemistry and its implication in enabling students face the challenges of global competitiveness in a world rapidly demanding individuals that possess 21st century competencies in the workforce. Two research questions and two null hypotheses guided the study. The study adopted a pre-test, post-test non-equivalent control group design. One hundred and forty-four Senior Secondary Class II students in Ihiala Local Government, Nnewi Education Zone, Anambra State Nigeria, participated in the study. The reliability of the instrument Mole Concept Interest Scale (MCIS) was 0.75. Mean and standard deviation were used to answer the research questions while analysis of covariance (ANCOVA) was used to test the hypotheses. Results of the study showed that 5E Piagetian Model did not only promote students‟ interest in the mole concept aspect of Chemistry but also encouraged the acquisition of generic and soft skills more than the traditional teaching methods. Gender was found to significantly affect students‟ interest in quantitative Chemistry. Recommendations arising from the study urged Chemistry teachers to recognize the responsibility of learners as the active agents of knowledge construction who own the prerogative to connect new knowledge to prior knowledge in their mental strictures, to think critically and to participate actively in the learning process. The teachers‟ roles as facilitators are meant to enable students effectively apply new knowledge that could help them build their capacity to face the challenges of life after school.